Toxic epidermal necrolysis in hepatitis A infection with acute-on-chronic liver failure: Case report and literature review - Zang, Xin; Chen, Si; Zhang, Lin; Zhai, Yongzhen (Frontiers in Medicine, 2022)
Toxic epidermal necrolysis (TEN) and Stevens-Johnson syndrome (SJS) are acute inflammatory skin adverse reactions characterized by epidermal exfoliation and multi-site mucositis, considered medical emergencies. The risk factors for SJS/TEN include immune disorders, malignancy, and genetic susceptibility. In most cases, medication is considered to be the leading cause of TEN. In addition, several studies suggest that infections such as the herpes simplex virus, human immunodeficiency virus (HIV), Mycoplasma pneumoniae, streptococcus, and meningococcus infections can be triggers for SJS/TEN. In this rare case, we share our experience managing toxic epidermal necrolysis in a hepatitis A virus infection with acute-on-chronic liver failure patient. A 38-year-old man who contracted active hepatitis A developed decompensated liver cirrhosis and progressed to acute-on-chronic liver failure. As the infection progressed, the target-like skin lesions accompanied by mucosal involvement worsened. His condition progressively worsened with a severe generalized rash, bullae and epidermal detachment accompanied by severe erosive mucosal lesions. The patient's skin detachment area gradually involved 30% of the body surface area, and the disease progressed to toxic epidermal necrolysis. The intravenous infusion of corticosteroids alleviated the patient's hypersensitivity, and the patient obtained a lasting remission without severe adverse reactions and complications.